Baitouweng Decoction Ameliorates Ulcerative Colitis in Mice Partially Attributed to Regulating Th17/Treg Balance and Restoring Intestinal Epithelial Barrier - Miao, Zhiwei; Chen, Liping; Feng, Hui; Gu, Mingjia; Yan, Jing; Xu, Yi; Ye, Bai (Frontiers in Pharmacology, 2021)
Ulcerative colitis (UC) is a chronic intestinal disease with unclear pathogenesis. With an increasing global prevalence over the past two decades, UC poses a serious threat to public health. Baitouweng decoction (BTW), a traditional Chinese medicine, has been shown to have good clinical efficacy for treating intestinal inflammation. Yet, the efficacy of BTW in UC and the underlying mechanism remain unclear. The current study aimed to determine whether BTW suppressed intestinal inflammation in mice and the potential mechanism. We used a dextran sulfate sodium (DSS)-induced murine colitis model to test the anti-inflammatory efficacy of BTW. Clinical symptoms were scored by the disease activity index (DAI), and the colon length and pathological changes in colon tissue were also used to further evaluate the efficacy of BTW. Precisely how BTW affected immune function and the intestinal barrier of UC mice was also examined. BTW significantly reduced DAI score and colonic pathological damage. BTW regulated the balance between T helper (Th)17 and regulatory T (Treg) cells, decreased interleukin (IL)-1β, IL-6, and tumor necrosis factor-α, and increased IL-10 levels. BTW reduced intestinal permeability of UC mice, increased expression of tight junction proteins (occludin and zonula occludens-1), and decreased expression of phospho-nuclear factor (p-NF)-κB and phospho-extracellular signal-regulated kinase (p-ERK) in the colon. BTW inhibited the ERK/p-NF-κB signaling pathway and suppressed expression of cyclo-oxygenase-2 and inducible NO synthase in lipopolysaccharide-activated RAW 264.7 cells. BTW significantly promoted the synthesis of short-chain fatty acids in the gut, particularly acetate, propionate, isobutyric acid, and isovalerate. The results suggest that BTW can protect against DSS-induced UC. The mechanism may be partially attributed to regulating the balance of Th17/Treg cells and restoring the intestinal epithelial barrier.